(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
There are author’s thoughts about fundamental things of entrepreneurship in this article. The focus is on the «human orientation» of economic activity, as long as in the centre of the life of society is a person itself, not the «profit». An essential analysis of the concept of «economic culture», its features and problems of its formation in Ukraine has been carried out in this work. The legislation of Ukraine establishes profit as the main goal of the enterprise activities. Thats why the essence of entrepreneurship is to maximise profits. The methods of increasing profits can be grouped and separated into different directions such as: expansion of production, reduced costs, access to new markets, increased productivity, minimise tax payments, investment activity. Ukrainian realities can have some groups which goes against the law such as: corruption, tax evasion, false privatisation, etc. Many Ukrainian entrepreneurs do not have a sense of responsibility for doing business, in other words we don’t have “culture of doing business». On the other hand, even if we will have some perfect law regarding business activities, it doesn’t mean the enterprise will perfectly follow it, unless the owner will be assured that the given law will be beneficial for the enterprise. Therefore, we want to focus our attention on the «economic culture» of entrepreneurs and emphasise on today’s relevance for Ukrainian economy. If to change the main vector of entrepreneurial activity from «profit» to «a human» – to reorient the goal of producing quality goods and services, to ensure decent working conditions «for employees», to care about the environment, to respect our country and those development programs which it provides» for the society». In other words such activity of the enterprise is «human oriented» and provides implementation of «economic culture».